Eradication of proliferative verrucous leukoplakia with toll-like receptor 7 agonist (topical imiquimod): a case report - Townsend, Melanie; Kejner, Alexandra E.; Nourollah-Zadeh, Farzad; Rizzante, Fabio A.P.; Woods, Tina R.; Rathore, Sonali; Alterman, Douglas; Teich, Sorin; Albergotti, William G.; Newman, Jason G.; Yoon, Angela J. (Frontiers in Oncology, 2024)
Proliferative verrucous leukoplakia (PVL) is an aggressive and distinct type of oral precancerous lesion characterized by warty surfaced white plaque diffusely involving oral mucosa. Surgical excision is the treatment of choice. However, PVL has persistent and recurrent growth patterns, requiring multiple surgical procedures. Surgical intervention is especially challenging if PVL extends between teeth limiting access. These interproximally located lesions have a high propensity to undergo malignant transformation. We report a case of a 53-year-old man with recurrent PVL diffusely covering the maxillary and mandibular gingiva. Despite complete surgical excisions, PVL recurred, and a focal area in the interproximal mandibular gingiva progressed to invasive squamous cell carcinoma requiring marginal resection. The remaining PVL areas were treated with topical imiquimod (toll-like receptor 7 agonist) for six months, resulting in complete clinical and histological resolution. Topical agents can cover a larger surface area and penetrate in between interproximal areas. Importantly, it allows for maximal local exposure with minimal systemic toxicity, essential for long-term treatment and prophylactic use of the agent to prevent relapse.